Impacts of Biochar on Physical Properties and Erosion Potential of a Mudstone Slopeland Soil - Zeng-Yei Hseu; Shih-Hao Jien; Wei-Hsin Chien; Ruei-Cheng Liou (The Scientific World Journal)
Food demand and soil sustainability have become urgent issues recently because of the global climate changes. This study aims to evaluate the application of a biochar produced by rice hull, on changes of physiochemical characteristics and erosion potential of a degraded slopeland soil. Rice hull biochar pyrolized at 400°C was incorporated into the soil at rates of 2.5%, 5%, and 10% (w/w) and was incubated for 168 d in this study. The results indicated that biochar application reduced the Bd by 12% to 25% and the PR by 57% to 92% after incubation, compared with the control. Besides, porosity and aggregate size increased by 16% to 22% and by 0.59 to 0.94 mm, respectively. The results presented that available water contents significantly increased in the amended soils by 18% to 89% because of the obvious increase of micropores. The water conductivity of the biochar-amended soils was only found in 10% biochar treatment, which might result from significant increase of macropores and reduction of soil strength (Bd and PR). During a simulated rainfall event, soil loss contents significantly decreased by 35% to 90% in the biochar-amended soils. In conclusion, biochar application could availably raise soil quality and physical properties for tilth increasing in the degraded mudstone soil.